Wheat in the Tropics : a growing demand - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1989)
Wheat was one of thee first plants to be cultivated by mankind, and today it is a major dietary constituent of about a quarter of the world's population, according to the International Wheat Council. It also dominates world cereal trade, with global...